Effectiveness of the acceptance and commitment therapy for resilience promotion in a non-clinical sample: A randomized controlled and a pilot study - Engin Büyüköksüz (BMC Psychology)
Abstract Background This research investigates the efficacy of Acceptance and Commitment Therapy (ACT) in fostering resilience among non-clinical adolescents. The prevailing socio-economic and psychological challenges have notably affected vulnerable demographics, particularly adolescents, thereby underscoring the importance of resilience for mental health. Methods This randomized controlled pilot study, carried out in Istanbul, sought to assess the effects of ACT interventions on resilience, self-compassion, and psychological flexibility in high school students. A total of 89 participants were assigned to either the ACT intervention group or a control group, with the intervention comprising six weekly sessions that emphasized key ACT principles, including mindfulness, emotional regulation, and self-compassion. Results Utilizing the Connor-Davidson Resilience Scale, Self-Compassion Scale, and Avoidance and Fusion Questionnaire, the findings indicated significant enhancements in resilience and self-compassion, alongside a decrease in psychological inflexibility within the ACT intervention group compared to the control group. Conclusion This pilot study provides preliminary evidence that ACT may be a promising approach for enhancing psychological resilience and self-compassion among adolescents. However, given the small sample size and baseline differences between groups, these findings should be interpreted with caution and warrant further investigation with larger, more diverse populations.